Walter Rosene bird calendar, Boone County, 1918-1927 - Rosene, Walter, 1880-1941et al (1918)
A ten year calendar of three hundred and eighty-one wild birds of Iowa annotated by Walter Rosene with sighting dates of species located in Boone County for the years 1918 through 1927. Also includes a record of two birds of North America not included in the Iowa list that were observed by Rosene. Bird observations from a trip to North Dakota in 1924 are included and noted with red ink. Nikon - camera